Sintesis dan Analisis Sifat Fisis Hidroton Berbasis Ball Clay dan Cocopeat Sebagai Media Tanam Hidroponik - Maulida Siti Maryam; Irfana Diah Faryuni; Mega Nurhanisa; Eneng Maryani (Jurnal Fisika FLUX, 2020)
ABSTRACT−Research on hydroton analysis based on ball clay and cocopeat has been conducted. This study aims to determine how the effect of cocopeat additionon physical properties of hydrotons in term of porosity, bulk density, and absorption.Cocopeat which were added to ball clay varies from 5%, 10%, 15%, 20%, and 25%. Hydroton were synthesized using a furnace at 950°C for 4 hours with a holding time for 2 hours. Based on the characterization results, the addition of cocopeat affected the physical properties of hydrotons, especially porosity and water absorbence of hydroton which were positively correlated 94.5% and 96% respectively. Meanwhile bulk density was negatively correlated 98.1%. The more cocopeat were added, the higher porosity and water absorbence, in contrary the bulk density decreased gradually.   KEYWORD : ball clay, cocopeat, hidroton